# Thread: dy/dx=e^(-x^2) - 2xy subject to y(2)=0

1. ## dy/dx=e^(-x^2) - 2xy subject to y(2)=0

hi,
need some help for this question, i tried solving by seperating dy to one side and dx to the other and integrating however dont get the right answer...how can i solve this
any help much appreciated

solve the following differential equation for y giving answer in form y=f(x)

dy/dx=e^(-x^2) - 2xy subject to y(2)=0

thankyou

2. The equation is linear in y, so use the integrating factor approach. What do you get?

3. i used the integrating factor method
integrating factor being e^(x^2)
i got the answer to be y=2/(e^(x^2))

y = (x-2)e^(-x^2)

4. Originally Posted by metalkakkarot
i used the integrating factor method
integrating factor being e^(x^2)
That is correct.

i got the answer to be y=2/(e^(x^2))

y = (x-2)e^(-x^2)

i did the question again and essentially had forgotten to integrate the RHS first time round...
now i get close to the correct answer except a sign difference...
at the end i subbed y=2 and x=0 to get c=2

6. Your working is correct up to the determination of the arbitrary constant. If you plug in x = 2, do you get y = 0? (I suspect you may have reversed the roles of x and y, perhaps?)

7. thankyou so much...it was as you said i had switched the x and the y and the end....got the answer

+thanks

8. You're very welcome. Have a good one!

,
,

,

,

,

,

,

,

,

,

,

,

,

,

# dyÃ·dx=2xy exÃ·x2 xeÃ—

Click on a term to search for related topics.